G83 Parent opinion on multi-disciplinary in-situ simulation as paediatric emergencies training. (27th April 2016) - Hart, C; Thompson, A; Bourke, T; Junk, C
Abstract : Aims: As a tertiary paediatric unit we conduct unannounced multi-disciplinary high-fidelity in-situ simulations. Team feedback has questioned how mock emergencies affect parents and children on the wards. In order to enhance our simulation programme and support families we have evaluated parental attitudes to ward-based simulated emergencies. Methods: Forty-one parent questionnaires were completed rating how strongly parents of inpatients agreed to statements about medical and nursing staff receiving training in managing emergencies. They were also asked how they and their child would be affected if this practice happened on the wards. Comments were gathered and on collection of the forms parents' questions were answered. A nurse and doctor involved in simulation distributed the questionnaires over two afternoons across seven wards and explained the concept of in-situ simulation to parents beforehand. Results: All parents who were approached agreed to participate and almost three quarters felt staff should have training in emergencies at least monthly. Only 17% of parents thought in-situ simulated emergencies would be distressing and this response varied depending on patient age and their admission frequency. One comment was that 'it would be stressful, but also necessary'. Almost all parents, over 90%, agreed that practicing for emergencies on the ward should be done even if it caused disruption. In addition, 95% of parents felt more confident in the team knowing this practice occurs, describing it as 'reassuring, essential'. Communication was a key parental concern. One parent stated that 'to be aware they could happen at any time would be enough for me not to become distressed'. Parents suggested providing an information leaflet on admission to prepare them for possible in-situ simulations and to 'have a quiet word in surrounding relatives ear' to inform parents and reduce distress. Conclusion: This survey provides valuable insight for those developing an in-situ simulation programme. Parents appear positive regarding ward-based training in paediatric emergencies; 'further training will only benefit my child'. This was even if there might be disruption and some distress generated, provided they were well informed. We are incorporating the parent suggestions into our simulation programme and aim to prospectively gather parental opinion post-simulations.